Sosialisasi Dampak Lingkungan Terhadap Penularan TB dan Filariasis di Negeri Hatuhenu Kecamatan Amahai Kabupaten Maluku Tengah - Souisa, Gracia Victoria; Vauza, Zukiflin P (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2018)
Negeri Hatuhenu, Amahai Sub-district, Central Maluku District, based on interviews with health officials and the government of the country, have various health problems such as clean and healthy living behavior, environmental sanitation problems that have an impact on the emergence of environment-based diseases such as tuberculosis, filariasis and malaria. To solve the above health problems, the lecturers and students of the Public Health Study Program in collaboration with health officials, the government of Hawahenu and Haatenu are conducting counseling on "Environmental Impacts on TB and Filariasis Transmission in Hawahenu State of Amahai Sub-district of Central Maluku" and public awareness to improve hygienic and healthy living behavior, improve environmental sanitation and preventive behavior of TB and filariasis transmission. The results of the service show that the community, the Government of Hawahenu, the Head of the Assembly of the Church and the tools of the ministry and the health staff of the Public Health Center and the Poskesdes Hengkenu Village responded positively and were greatly helped by the socialization activities in the effort to increase the knowledge of the community and the mass treatment that has been done.